A new approach for the prediction of fatigue life in rolling bearings based on damage accumulation theory considering residual stresses - Hwang, Jae-Il; Poll, Gerhard (Frontiers in Manufacturing Technology, 2022)
Today, the service life of rolling bearings is standardized in ISO 281, based on the theory of Lundberg and Palmgren. The material properties such as fatigue limit stress were taken into account by introducing the fatigue limit stress proposed by Ioannides and Harris. The standard calculation model provides a reasonable range of fatigue life in good agreement with experimental results under ideal test conditions such as constant external load magnitude. However, as the operating conditions of bearings become more complex with advances in technology, bearings are exposed to varying loads and oscillating motion. Therefore, a new analytical calculation model that can predict the fatigue life of rolling bearings operating under these conditions is needed. In the proposed approach in this study, the fatigue life is determined based on the Palmgren-Miner linear damage rule, evaluating the subsurface stresses below the rolling contact using the S-N curve according to the fatigue criterion proposed by Lundberg and Palmgren. All rolling contacts that occur in an internal stress cycle due to the internal dynamic behavior during rotating operations are evaluated individually and referred to as partial damage risks. The partial damage risks are accumulated linearly according to the Palmgren-Miner theory to obtain the load cycle to failure consequently. At this time, the loaded volume is assessed along the depth from the contact area to the core of the bearing ring, which makes it possible to indicate the depth position of fatigue occurrence in terms of crack initiation. The material properties such as the fatigue limit stress and the probability of failure are taken from the S-N curve itself. To consider the residual stress, a simple concept is suggested by using the ratio of the maximum contact pressure to the yield criteria. The proposed approach can be extended to calculate oscillating fatigue life regarding the number of rolling contacts at a given oscillation amplitude. The calculation results according to ISO 281 are compared with the results obtained by using the proposed approach, which shows a good agreement with the calculation results obtained by using ISO 281.